Trends and Directions in Global Student Mobility - Bhandari, Rajika; Belyavina, Raisa (International Higher Education, 2012)
Drawing upon two recent publications, this article highlights some trends in student mobility, including the emergence of new players, the shift from brain drain' to brain gain' and brain circulation', language as a key driver for study overseas, and new internationalization policies that are re-mapping the flow of global talent. The article also explores the expanding definition of mobility that will likely have an impact on global student flows in the near future.